Handbook of Islamic Sects and Movements - Daniah, Izza Annafisatud (Universitas Islam Internasional Indonesia, 2022)
Edited by. Muhammad Afzal Upal and Carole M. CusackBrill, 2021With more than 1,8 billion followers, Islam is the second largest religion in the world. As a faith, Islam is often referred to as al-deen, which is derived from the diversity of its thought. Islam will always face dynamic changes from within and at the same time will have to deal with various advances in civilization, such as modernization, states as well as social, cultural and political developments at different points in time. As a result, Islam and Islamic thought are differentiated from one another. Islam is a revelation from God and immutable, while Islamic thought is a subjective truth according to one's understanding of the objective of revelation. The spread of various sects and movements in Islam has shown that Islamic thought is in a constant state of development and does not remain static. Moreover, because Islam has spread throughout the world, it is embedded and developing in a variety of peoples and cultures, from Africa to Asia and beyond.